RESTRICTIONS ON THE VOTING RIGHTS OF FORMER CORRUPTOR CONSTITUTIONS - Usfunan, Maria Virginia (Faculty of Law, Khairun University, 2023)
One form of popular sovereignty is through general elections. This is evidenced by the provisions of Article 1 point 1 of Law Number 7 of 2017 concerning General Elections (Election Law) which stipulates